Does Breast Milk Nurture T Lymphocytes in Their Cradle? - Hsu, Peter S.; Nanan, Ralph (Frontiers in Pediatrics, 2018)
Breast feeding has been associated with improved infant outcomes in multiple aspects, including immune outcomes such as infections and potentially atopy and autoimmunity. However associations do not necessarily implicate cause and effect and at this point, exactly how breast feeding and components of breast milk may modulate the infant’s immune compartment remains unclear, especially in humans. Some lines of evidence suggest that breastfeeding affects the development of the infant’s thymus, a critical organ for T cell development. This may be a direct effect mediated by breast milk components or alternatively, a secondary effect from the impact of breast feeding on the infant’s gut microbiome. Here we discuss the potential mechanisms and impact of this association between breast feeding and thymic development.